2010
DOI: 10.2169/internalmedicine.49.3364
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Habit of Cigarette Smoking and Airflow Limitation in Healthy Japanese Individuals: The Takahata Study

Abstract: Background Chronic obstructive pulmonary disease (COPD) is characterized by chronic airflow limitation. The prevalence of airflow limitation in Japan is 10.9% (16.4% of males and 5.0% of females). Cigarette smoking is well known as a major cause of COPD. However, few epidemiological studies have evaluated the effects of cigarette smoking on pulmonary function in healthy subjects. Methods Subjects aged 40 years or older (n=2,917), who had participated in a community-based annual health check in Takahata, Japan,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 21 publications
5
57
2
Order By: Relevance
“…Although there have been only a few population-based surveys regarding the prevalence of COPD in Japan, these figures are a little higher than those reported in the Nippon COPD Epidemiology (NICE) study, in which the prevalence defined by the fixed ratio was 10.9% [20]. Similarly, in a community-based annual health check, Osaka et al [18] also reported that 10.6% had COPD as defined by the fixed ratio and 6.4% had COPD The serum 25-hydroxyl vitamin D concentration was not different between COPD and non-COPD subjects; COPD: Chronic obstructive pulmonary disease; LLN: Lower limit of normal. as defined by the LLN.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Although there have been only a few population-based surveys regarding the prevalence of COPD in Japan, these figures are a little higher than those reported in the Nippon COPD Epidemiology (NICE) study, in which the prevalence defined by the fixed ratio was 10.9% [20]. Similarly, in a community-based annual health check, Osaka et al [18] also reported that 10.6% had COPD as defined by the fixed ratio and 6.4% had COPD The serum 25-hydroxyl vitamin D concentration was not different between COPD and non-COPD subjects; COPD: Chronic obstructive pulmonary disease; LLN: Lower limit of normal. as defined by the LLN.…”
Section: Discussionmentioning
confidence: 84%
“…The LLN for the Japanese population was calculated using the method described by Osaka et al [18]. The participants also answered additional questions to investigate their smoking status and history.…”
Section: Introductionmentioning
confidence: 99%
“…The details and analyses of FVC, FEV1 and FEV1/FVC in these subjects have been described previously (17). Most subjects did not report a history of pulmonary disease (17). Ten and eight percent of the subjects in this study population had airflow limitation and lung restriction, respectively (17,21).…”
Section: Study Populationmentioning
confidence: 85%
“…This study was based on a secondary analysis of data that has been previously analyzed and reported (17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation